Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Absolutely, let's solve the problem step-by-step!
### Given functions:
[tex]\[ f(x) = 5x - 1 \][/tex]
[tex]\[ g(x) = 5x^2 - 1 \][/tex]
### Part (a): [tex]\( (f \circ g)(x) \)[/tex]
Denote [tex]\( (f \circ g)(x) \)[/tex] as [tex]\(f(g(x))\)[/tex]. This means we need to substitute [tex]\(g(x)\)[/tex] into [tex]\(f(x)\)[/tex]:
1. Find [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = 5x^2 - 1 \][/tex]
2. Substitute [tex]\(g(x)\)[/tex] into [tex]\(f(x)\)[/tex]:
[tex]\[ f(g(x)) = f(5x^2 - 1) \][/tex]
3. Substitute [tex]\(5x^2 - 1\)[/tex] into the function [tex]\(f(x)\)[/tex]:
[tex]\[ f(5x^2 - 1) = 5(5x^2 - 1) - 1 \][/tex]
4. Simplify:
[tex]\[ f(5x^2 - 1) = 25x^2 - 5 - 1 = 25x^2 - 6 \][/tex]
Thus,
[tex]\[ (f \circ g)(x) = 25x^2 - 6 \][/tex]
### Part (b): [tex]\( (g \circ f)(x) \)[/tex]
Denote [tex]\((g \circ f)(x)\)[/tex] as [tex]\(g(f(x))\)[/tex]. This means we need to substitute [tex]\(f(x)\)[/tex] into [tex]\(g(x)\)[/tex]:
1. Find [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = 5x - 1 \][/tex]
2. Substitute [tex]\(f(x)\)[/tex] into [tex]\(g(x)\)[/tex]:
[tex]\[ g(f(x)) = g(5x - 1) \][/tex]
3. Substitute [tex]\(5x - 1\)[/tex] into the function [tex]\(g(x)\)[/tex]:
[tex]\[ g(5x - 1) = 5(5x - 1)^2 - 1 \][/tex]
4. Simplify:
[tex]\[ (5x - 1)^2 = 25x^2 - 10x + 1 \][/tex]
[tex]\[ g(5x - 1) = 5(25x^2 - 10x + 1) - 1 = 125x^2 - 50x + 5 - 1 = 125x^2 - 50x + 4 \][/tex]
Thus,
[tex]\[ (g \circ f)(x) = 125x^2 - 50x + 4 \][/tex]
### Part (c): [tex]\( (f \circ g)(1) \)[/tex]
We found in part (a) that [tex]\( (f \circ g)(x) = 25x^2 - 6 \)[/tex]. Now we evaluate this at [tex]\( x = 1 \)[/tex]:
[tex]\[ (f \circ g)(1) = 25(1)^2 - 6 = 25 - 6 = 19 \][/tex]
Thus,
[tex]\[ (f \circ g)(1) = 19 \][/tex]
### Part (d): [tex]\( (g \circ f)(1) \)[/tex]
We found in part (b) that [tex]\( (g \circ f)(x) = 125x^2 - 50x + 4 \)[/tex]. Now we evaluate this at [tex]\( x = 1 \)[/tex]:
[tex]\[ (g \circ f)(1) = 125(1)^2 - 50(1) + 4 = 125 - 50 + 4 = 79 \][/tex]
Thus,
[tex]\[ (g \circ f)(1) = 79 \][/tex]
### Summary of Results
a. [tex]\( (f \circ g)(x) = 25x^2 - 6 \)[/tex]
b. [tex]\( (g \circ f)(x) = 125x^2 - 50x + 4 \)[/tex]
c. [tex]\( (f \circ g)(1) = 19 \)[/tex]
d. [tex]\( (g \circ f)(1) = 79 \)[/tex]
### Given functions:
[tex]\[ f(x) = 5x - 1 \][/tex]
[tex]\[ g(x) = 5x^2 - 1 \][/tex]
### Part (a): [tex]\( (f \circ g)(x) \)[/tex]
Denote [tex]\( (f \circ g)(x) \)[/tex] as [tex]\(f(g(x))\)[/tex]. This means we need to substitute [tex]\(g(x)\)[/tex] into [tex]\(f(x)\)[/tex]:
1. Find [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = 5x^2 - 1 \][/tex]
2. Substitute [tex]\(g(x)\)[/tex] into [tex]\(f(x)\)[/tex]:
[tex]\[ f(g(x)) = f(5x^2 - 1) \][/tex]
3. Substitute [tex]\(5x^2 - 1\)[/tex] into the function [tex]\(f(x)\)[/tex]:
[tex]\[ f(5x^2 - 1) = 5(5x^2 - 1) - 1 \][/tex]
4. Simplify:
[tex]\[ f(5x^2 - 1) = 25x^2 - 5 - 1 = 25x^2 - 6 \][/tex]
Thus,
[tex]\[ (f \circ g)(x) = 25x^2 - 6 \][/tex]
### Part (b): [tex]\( (g \circ f)(x) \)[/tex]
Denote [tex]\((g \circ f)(x)\)[/tex] as [tex]\(g(f(x))\)[/tex]. This means we need to substitute [tex]\(f(x)\)[/tex] into [tex]\(g(x)\)[/tex]:
1. Find [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = 5x - 1 \][/tex]
2. Substitute [tex]\(f(x)\)[/tex] into [tex]\(g(x)\)[/tex]:
[tex]\[ g(f(x)) = g(5x - 1) \][/tex]
3. Substitute [tex]\(5x - 1\)[/tex] into the function [tex]\(g(x)\)[/tex]:
[tex]\[ g(5x - 1) = 5(5x - 1)^2 - 1 \][/tex]
4. Simplify:
[tex]\[ (5x - 1)^2 = 25x^2 - 10x + 1 \][/tex]
[tex]\[ g(5x - 1) = 5(25x^2 - 10x + 1) - 1 = 125x^2 - 50x + 5 - 1 = 125x^2 - 50x + 4 \][/tex]
Thus,
[tex]\[ (g \circ f)(x) = 125x^2 - 50x + 4 \][/tex]
### Part (c): [tex]\( (f \circ g)(1) \)[/tex]
We found in part (a) that [tex]\( (f \circ g)(x) = 25x^2 - 6 \)[/tex]. Now we evaluate this at [tex]\( x = 1 \)[/tex]:
[tex]\[ (f \circ g)(1) = 25(1)^2 - 6 = 25 - 6 = 19 \][/tex]
Thus,
[tex]\[ (f \circ g)(1) = 19 \][/tex]
### Part (d): [tex]\( (g \circ f)(1) \)[/tex]
We found in part (b) that [tex]\( (g \circ f)(x) = 125x^2 - 50x + 4 \)[/tex]. Now we evaluate this at [tex]\( x = 1 \)[/tex]:
[tex]\[ (g \circ f)(1) = 125(1)^2 - 50(1) + 4 = 125 - 50 + 4 = 79 \][/tex]
Thus,
[tex]\[ (g \circ f)(1) = 79 \][/tex]
### Summary of Results
a. [tex]\( (f \circ g)(x) = 25x^2 - 6 \)[/tex]
b. [tex]\( (g \circ f)(x) = 125x^2 - 50x + 4 \)[/tex]
c. [tex]\( (f \circ g)(1) = 19 \)[/tex]
d. [tex]\( (g \circ f)(1) = 79 \)[/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.